Identification of a novel isoform of Slc26a4 by single-cell RNA-sequencing of pendrin-expressing cells in the cochlea - Jin-Young Koh; Corentin Affortit; Kazuaki Homma; Satoe Takahashi; Jonathan M. Nizar; Paul T. Ranum; Rose Gogal; Eun-Mi Kim; Minkyung Kang; Diana L. Kolbe; Fengxiao Bu; Cody West; et al. (Human Genetics, 2026)
Pathogenic variation of SLC26A 4 gene causes both Pendred syndrome (PDS) and non-syndromic enlarged vestibular aqueduct (NSEVA/DFNB4), two autosomal recessive disorders. The former accounts for approximately 6% of human genetic hearing loss, making it the second most common form of syndromic deafness after Usher syndrome, while the latter is the most common radiological malformation associated with childhood sensorineural hearing loss (SNHL). Here, we used short- and long-read single-cell RNA sequencing (scRNA-seq) of pendrin-expressing cells in the murine cochlea to identify a novel short isoform of Slc26a4 . We demonstrate that the short Slc26a4 isoform is expressed in both the inner ear and kidney and investigate its interactions and functions. We also characterize the genotype-phenotype association for SLC26A4 -related hearing loss in the context of these two isoforms. These results provide a new reference for molecular profiling of pendrin and offer novel insights into cell-type-specific splicing events and SLC26A4 -related hearing loss.